Feeding Diversity of Myllocerus viridanus Fab. (Coleoptera: Curculionidae) from South India - Ahmad, Mukhtar (Indian Forester, 1989)
Myllocerus viridanus Fab. (Coleoptera: Curculionidae) is a common defoliator of teak (Tectona grandis) in the forests of Southern India. It is a potential pest with distinct polyphagous nature. It has been recorded causing considerable defoliation to many plant species of forestry importance wbich include herbs (Cassia tara and Solanum violacium), shrubs (Calliandra calothyrsus, Cassia hirsuta, Helicteres isora L.) and trees like Acacia auriculiformis, Cassia fistula, Eugenia jambolana, Eucalyptus robusta, Pongamia pinnata, Populus deltoides, Sapindus tripliatus and Eupatorium odoratum weed.